2018
DOI: 10.1542/peds.2018-1009
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen and Febrile Seizure Recurrences During the Same Fever Episode

Abstract: To confirm the safety of using acetaminophen for febrile seizures (FSs) and to assess its efficacy in preventing FS recurrence during the same fever episode. METHODS: In this single-center, prospective, open, randomized controlled study, we included children and infants (age range: 6-60 months) with FSs who visited our hospital between May 1, 2015, and April 30, 2017. The effectiveness of acetaminophen was examined by comparing the recurrence rates of patients in whom rectal acetaminophen (10 mg/kg) was admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 19 publications
2
21
0
3
Order By: Relevance
“…Interestingly, one trial found that antipyretics are ineffective in lowering the temperature at all during febrile episodes that are associated with febrile seizure [ 138 ]. However, a recent study concluded that rectal paracetamol administration significantly decreased the likelihood of recurrent febrile seizures during the same fever episode [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one trial found that antipyretics are ineffective in lowering the temperature at all during febrile episodes that are associated with febrile seizure [ 138 ]. However, a recent study concluded that rectal paracetamol administration significantly decreased the likelihood of recurrent febrile seizures during the same fever episode [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that use of paracetamol combined with tepid sponging was more effective in bringing down the temperature than using paracetamol alone. 7 A prospective study conducted to questionnaire-based study to evaluate the knowledge, attitude and practice of mothers of under-five children suffering with febrile convulsion at the Mofid children hospital. Sample consisted of 126 mothers of children with febrile convulsion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The cumulative incidence of FS is estimated to be 2-4 % in the United States and 8-10 % in Japan [2,3]. The risk of recurrence during the same febrile illness has been reported as around 15 % [4,5], and recurrence usually occurs within 24 h [6,7]. Prophylactic diazepam was previously widely administered to children with FS according to the clinical practice guideline for FS in Japan [8].…”
Section: Introductionmentioning
confidence: 99%